Evaluation of the effect of skin cleaning procedures on the dermal absorption of chemicals. Issue 5 (August 2015) - Dennerlein, Kathrin; Jäger, Thomas; Göen, Thomas; Kilo, Sonja; Schaller, Karl Heinz; Drexler, Hans; Korinth, Gintautas
Highlights The effectiveness of two skin cleaning techniques after exposure to chemicals was investigated. The penetration through, but also the accumulation in the skin should be considered for risk assessment of chemicals. Skin cleaning with water reduces the penetration of hydrofluoric acid through and its deposition in the skin. The presented cleaning protocol could serve as an approach in the standardization of ex vivo skin decontamination studies.